Windows 10 bible - Tidrow, Rob; Boyce, Jim, 1958-; Shapiro, Jeffrey R. (Online access with DDA: Askews (Maths), 2015)
A complete, detailed Windows 10 reference for beginners and power users alike. The authors tell you everything you could ever hope to know about the Windows operating system. Step-by-step instructions walk you through new and important procedures, and screen shots help you stay on track every step of the way.